Development and Testing of the Test of Functional Health Literacy in Dentistry (TOFHLiD) - Debra A. Gong, DDS, MA; Jessica Y. Lee, DDS, MPH, PhD; R. Gary Rozier, DDS, MPH; (Blackwell Synergy, 2007)
This study aims to evaluate the reliability and validity of the Test of Functional Health Literacy in Dentistry (TOFHLiD), a new instrument to measure functional oral health literacy.